2020
DOI: 10.1136/bmjopen-2020-039426
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on mental health of young people and adults: a systematic review protocol of observational studies

Abstract: IntroductionSince the WHO declared COVID-19 as a pandemic, the spread of the new coronavirus has been the focus of attention of scientists, governments and populations. One of the main concerns is the impact of this pandemic on health outcomes, mainly on mental health. Even though there are a few empirical studies on COVID-19 and mental health, so far, there is no systematic review about the impact of COVID-19 on mental health of young people and adults yet. We aim to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 40 publications
5
87
0
3
Order By: Relevance
“…Undoubtedly, working in such unprecedented times would affect one's mental well-being. 5 A study undertaken in Singapore found HCWs suffered from a high level of psychological distress and represent a vulnerable group where psychological intervention may be beneficial. 6 With this in mind, our study aims to understand the psychological impact of the COVID-19 pandemic among HCWs at acute hospital settings in the South-East of Ireland, as a crucial step in guiding policies and interventions to maintain their psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, working in such unprecedented times would affect one's mental well-being. 5 A study undertaken in Singapore found HCWs suffered from a high level of psychological distress and represent a vulnerable group where psychological intervention may be beneficial. 6 With this in mind, our study aims to understand the psychological impact of the COVID-19 pandemic among HCWs at acute hospital settings in the South-East of Ireland, as a crucial step in guiding policies and interventions to maintain their psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…The SMD was chosen as a measure of the pooled results considering the likely variability in the measuring scales for continuous outcomes. 42 The effect size will be interpreted by Cohen’s proposal: 0.20 corresponds to a small effect size, 0.50 corresponds to a medium effect size and 0.80 corresponds to a large effect size. 43 …”
Section: Methods and Analysismentioning
confidence: 99%
“…The SMD was chosen as a measure of the pooled results considering the likely variability in the measuring scales for continuous outcomes. 42 The effect size will be interpreted by Cohen's proposal: 0.20 corresponds to a small effect size, 0.50 corresponds to a medium effect size and 0.80 corresponds to a large effect size. 43 A random effects model will be selected under the assumption that the studies included in the metaanalysis were carried out with heterogeneous populations.…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse cenário incerto e sem precedentes, imposto pela atual pandemia da Covid-19, grupos de pesquisa e profissionais de saúde têm se preocupado em reunir e fornecer recomendações sobre adaptações razoáveis e seguras para serem aplicadas nos serviços de oncologia, protegendo não só o paciente, como também suas famílias e a equipe de saúde interdisciplinar no cuidado ao câncer 18,19,22,23 . Um exemplo disso é o guia clínico internacional publicado como relato especial na revista Pediatric Blood & Cancer 18 , que reuniu informações das principais organizações de câncer infantojuvenil, tais como a International Society for Pediatric Oncology (SIOP), o Children's Oncology Group (COG) e o St. Jude Global, o qual forneceu orientações de adaptações que poderão ajudar a gerenciar as demandas da pandemia e nortear preparações para os impactos a longo prazo, como diagnósticos tardios 18 .…”
Section: Desenvolvimentounclassified